Pengaruh Filosofi Dalihan Na Tolu Sebagai Sistem Moral Batak Terhadap Implementasi Karakter Kristen Dari Perspektif Sahala - Michael Theofilus; Riris Johanna Siagian (Sekolah Tinggi Teologi Baptis Indonesia, 2026)
This research was conducted to understand the relationship between the Dalihan na tolu culture and the Christian faith amid ongoing debates within the Batak Christian community over the role of culture in believers' lives. The research was conducted in the city of Pekanbaru among HKBP clergy, consisting of pastors, church teachers, elders, prospective pastors, and prospective deacons. This study employed a qualitative approach, using open-ended interviews with informants to collect data. Data analysis was conducted using the Miles and Huberman model, with the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that dalihan na tolu is understood as a moral system of the Batak Toba community that serves to maintain social harmony through the values of mutual respect, appreciation, and strengthening brotherhood. Dalihan na tolu is also viewed as connected to Christian values, particularly in teachings of love, respect for others, and a peaceful life. However, the practice of dalihan na tolu must still be carried out proportionally so that respect for culture doesn’t evolve into syncretism. This study provides a novel perspective by positioning dalihan na tolu not only as a customary and moral system of the Batak people but also as a space for dialogue between Batak Toba culture and the formation of Christian character through the sahala perspective. Thus, this study demonstrates that local culture can serve as a medium for character building and growth of Christian faith when interpreted critically, contextually, and theologically.